Geodemography: Geospatial Stream of Demographic Analysis - Gnyawali, Bishal; Sigdel, Uddhav (Janajyoti Journal, 2025)
Geo-demography, an emergent subfield at the intersection of geography and demography, integrates spatialtechnologies such as Geographic Information Systems (GIS), remote sensing, and spatial statistics to enhancethe understanding of population dynamics within their spatial and socio-environmental contexts. Thiscomprehensive review critically examines the theoretical foundations, methodological innovations, analyticaltechniques, and diverse applications of geo-demography in urban planning, public health, market segmentation,and disaster management, with a regional focus on South Asia. Employing a qualitative meta-synthesisapproach and adhering to PRISMA guidelines, the study synthesizes 30 key scholarly works selected fromglobal academic databases. It highlights how geo-demography contributes to spatially informed and equitabledecision-making by revealing patterns in migration, urbanization, health disparities, and service accessibility.However, the review also identifies critical gaps, including inconsistent data quality, lack of methodologicalstandardization, limited application in rural and low-income settings, and ethical concerns related to privacy andsurveillance. It underscores the need for participatory approaches, interdisciplinary collaboration, and theintegration of critical geographic perspectives to address spatial inequalities and demographic vulnerabilities.Looking ahead, the review advocates for the incorporation of Artificial Intelligence (AI), real-time data, andethical data governance to expand the scope and impact of geo-demography in the Global South. Ultimately, thestudy positions geo-demography as a vital tool for sustainable development, digital governance, and inclusivepolicy-making in an increasingly spatially complex world.